In vitro activity of enterocin AP-CECT7121 against multi-resistant Staphylococcus aureus biofilms - Delpech, Gastón (2017)
Background: The pathogen Staphylococcus aureus is able to persist on biotic andabiotic surfaces through biofilm formation. Enterocin AP-CECT7121 has shownhomogenous bactericidal activity in vitro against Staph. aureus of food and clinicalorigin. Objective: assess the eradication of biofilm-associated cells of multiresistant clinical Staph. aureus. Methods: 7 multi-resistant Staph. aureus(HSSA32-HSSA38) isolated from blood cultures of inpatients, from Hospital RamónSantamarina (Tandil City, Argentina) during the period January-November 2016were studied. All included patients had hip prosthesis infections. Purified APCECT7121 was used. MICs determinations were done by the micro-liquid dilutionmethod. For bactericidal activity against planktonic cells, AP-CECT7121 wasadded to staphylococcal cultures (108 CFU/mL), in a 96-well plate, to finalconcentrations of 1xMIC and 4xMIC, and incubated at 37°C. CFU counts wereperformed at 0, 4, 8, and 24 h. For assessing bactericidal activity against Staph.aureus biofilm cells, staphylococcal suspensions in Brain Heart Infusion broth-1%glucose were added to the wells and incubated for 24 h at 37°C. Formed biofilmswere incubated with the enterocin (1XMIC and 4XMIC) for 1 and 24 h. After, CFUcounts of the biofilms were done. Results: bactericidal activity of AP-CECT7121against planktonic cell was detected between 1- 4 h of incubation. A dosedependent effect of AP-CECT7121 against staphylococcal biofilms was observed.AP-CECT7121 (4XMIC) showed bactericidal activity against biofilm cells, butcomplete killing was not achieved. Conclusion: AP-CECT7121 showed a significantefficacy against staphylococcal biofilms and constitutes a candidate for futureapplications in the prevention and treatment of biofilm-associated infections